2012
DOI: 10.4244/eijv8i6a114
|View full text |Cite
|
Sign up to set email alerts
|

Vascular responses to a biodegradable polymer (polylactic acid) based Biolimus A9-eluting stent in porcine models

Abstract: The level of endothelial coverage in BioPol-BES was comparable to BMS at four weeks, with no significant increase of inflammatory reaction up to 15 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Animal studies have shown significantly lower inflammatory responses in the stented segments, and the rapid recovery of endothelial function of peri-stent segments in the biodegradable polymer BES group compared with the durable polymer DES group at 1 month [33] . Also, the level of endothelial coverage in biodegradable polymer BES was comparable to BMS at four weeks, with no significant increase in inflammatory reactions up to 15 months [34] . These observations may explain why the biodegradable polymer BES may be associated with a lower risk of very late ST and a better long-term outcome in our meta-analysis.…”
Section: Discussionmentioning
confidence: 79%
“…Animal studies have shown significantly lower inflammatory responses in the stented segments, and the rapid recovery of endothelial function of peri-stent segments in the biodegradable polymer BES group compared with the durable polymer DES group at 1 month [33] . Also, the level of endothelial coverage in biodegradable polymer BES was comparable to BMS at four weeks, with no significant increase in inflammatory reactions up to 15 months [34] . These observations may explain why the biodegradable polymer BES may be associated with a lower risk of very late ST and a better long-term outcome in our meta-analysis.…”
Section: Discussionmentioning
confidence: 79%
“…Hagiwara reported that inflammatory score and injury score in BES were comparable to even bare metal stent at 30 days in histological analysis [17]. It is also reported that fibrin scores were significantly greater for both SES and paclitaxel-eluting stents (PES) compared with their respective bare metal stent controls at 30 days [18].…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…Three to four months are required for complete endothelialization with BMS 28 , 29 , whereas with DES, more time is required 6 . At the same time, the level of endothelial coverage in BP- BES was comparable to that of BMS at four weeks, with no significant increase in inflammatory reactions up to 15 months 30 . Moreover, compared with DP-DES, BP-BES contains a biodegradable polymer that gradually dissolves into water and carbon dioxide, which are associated with a lower risk of inflammatory responses in animal studies 31 .…”
Section: Discussionmentioning
confidence: 65%